USE OF SMART NOSE AND GC/MS/O ANALYSIS TO DEFINE VOLATILE FINGERPRINT OF A GOATSKIN BAG CHEESE “BOUHEZZA” - Zitoun-Hamama, Ouarda Aissaoui; Carpino, Stefania; Rapisarda, Teresa; Belvedere, Giovanni; Licitra, Giuseppe; Zidoune, Mohammed Nasser Eddine (Emirates Journal of Food and Agriculture, 2016)
Bouhezza is an Algerian ripened cheese manufactured specifically in a goatskin bag with “Lben”, salt and raw milk for several weeks. The aim of this study was to characterize the unknown aromatic profile of the Bouhezza using SMart Nose, gas chromatography/mass spectrometry (GC/MS) and GC/MS/Olfactometry. In a first step, four farmhouse Bouhezza cheeses were analyzed by SMart Nose and by GC/MS to investigate volatile profile at 75 and 150 ripening days. In a second step, two Bouhezza cheeses produced under controlled conditions according to the traditional process were analyzed during manufacturing-ripening by GC/MS/Olfactometry, to detect odor active compounds changes. Results showed higher variability of volatiles in cheeses at 75 days ripening compared to 150 days. Farmhouse and experimental cheeses showed esters the most abundant volatile compounds detected with GC/MS and GC/MS/Olfactometry. Ten odor active compounds were common between cheeses whatever is the origin or the age. These compounds can be considered as marker of the aromatic profile of Bouhezza cheese, not yet established